Reflection of Reality and Unreality in the Sanitation Sector in Nepal - Limbu, Lila Prasad (Humanities and Social Sciences Journal, 2023)
This study, explores the development trend of sanitation coverage and compares and contrasts government reports and the reality of the sanitation sector. The researcher has used a descriptive research design and a quantitative research method. The data collection technique was field observation because the researcher observed 228 houses to find the reality of having and not having toilet households. The researcher found that the Nepal Government’s record of sanitation coverage is not real because the Nepal Government claimed cent percent of households have toilets in the study area. But it was found that 60% of households do not have toilets. However, this study does not cover factors of sanitation. The other factors need further study.